Inhibition of PPARγ by BZ26, a GW9662 derivate, attenuated obesity-related breast cancer progression by inhibiting the reprogramming of mature adipocytes into to cancer associate adipocyte-like cells - Li, Liangge; Geng, Jiafeng; Yu, Wen; Zhou, Feifei; Zheng, Zhihuan; Fu, Kaiyue; Kong, Junjie; Feng, Xiujing (Frontiers in Pharmacology, 2023)
Obesity has been associated with the development of 13 different types of cancers, including breast cancer. Evidence has indicated that cancer-associated adipocytes (CAAs) promote the proliferation, invasion, and metastasis of cancer. However, the mechanisms that link CAAs to the progression of obesity-related cancer are still unknown. Here, we found the mature adipocytes in the visceral fat of HFD-fed mice have a CAAs phenotype but the stromal vascular fraction (SVF) of the visceral fat has not. Importantly, we found the derivate of the potent PPAR antagonist GW9662, BZ26 inhibited the reprogramming of mature adipocytes in the visceral fat of HFD-fed mice into CAA-like cells and inhibited the proliferation and invasion of obesity-related breast cancer. Further study found that it mediated the browning of visceral, subcutaneous and perirenal fat and attenuated inflammation of adipose tissue and metabolic disorders. For the mechanism, we found that BZ26 bound and inhibited PPAR by acting as a new modulator. Therefore, BZ26 serves as a novel modulator of PPAR activity that is capable of inhibiting obesity-related breast cancer progression by inhibiting of CAA-like cell formation, suggesting that inhibiting the reprogramming of mature adipocytes into CAAs or CAA-like cells may be a potential therapeutic strategy for obesity-related cancer treatment.